Frozen Shoulder - Anggun Budi Wardani; Risal Wintoko (Medula, 2021)
Frozen shoulder or also known as adhesive capsulitis is a shoulder pain disorder that It is caused by thickening and tightening of the connective tissue capsule around the shoulder joint. The most common risk factors are age > 40 years, women > men as much as 70%, recent trauma such as surgery or fracture of the arm can cause immobility during recovery. Typical in frozen shoulder, there is progressive shoulder stiffness, severe pain (especially at night) and almost complete loss of passive and active external rotation of the shoulder. In the history, it is necessary to know the onset and duration of symptoms, location, function, and previous trauma. On physical examination, deltoid and supraspinatus atrophy can be found in the old case, the arm can be adducted and turned inward and painful when pressed. Plain radiography, ultrasound, and MRI investigations. Management is carried out both non-operatively to help relieve pain and relieve inflammation in the early phase by administering NSAIDs, corticosteroids (oral/injection), physiotherapy and cryotherapy. Surgical management may be considered if previous conservative efforts have failed.